2016
DOI: 10.1038/srep18971
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen regulates gene expression by modifying the free radical chain reaction-dependent generation of oxidized phospholipid mediators

Abstract: We previously showed that H2 acts as a novel antioxidant to protect cells against oxidative stress. Subsequently, numerous studies have indicated the potential applications of H2 in therapeutic and preventive medicine. Moreover, H2 regulates various signal transduction pathways and the expression of many genes. However, the primary targets of H2 in the signal transduction pathways are unknown. Here, we attempted to determine how H2 regulates gene expression. In a pure chemical system, H2 gas (approximately 1%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 46 publications
3
71
0
Order By: Relevance
“…Ohsawa et al, 2007;Buchholz et al, 2008;Huang et al, 2010;Taura et al, 2010;Kawaguchi et al, 2014;Iuchi et al, 2016), and proved that H 2 could react directly with cytotoxic ROS due to its ability to rapidly diffuse across membranes (Ohsawa et al, 2007;Taura et al, 2010;Iuchi et al, 2016). Consistently, in our experiments, H 2 alleviated B-induced lipid peroxidation and H 2 O 2 overproduction (Fig.…”
Section: Hydrogen Alleviated Boron Toxicity By Modulating Ros Homeostsupporting
confidence: 89%
See 1 more Smart Citation
“…Ohsawa et al, 2007;Buchholz et al, 2008;Huang et al, 2010;Taura et al, 2010;Kawaguchi et al, 2014;Iuchi et al, 2016), and proved that H 2 could react directly with cytotoxic ROS due to its ability to rapidly diffuse across membranes (Ohsawa et al, 2007;Taura et al, 2010;Iuchi et al, 2016). Consistently, in our experiments, H 2 alleviated B-induced lipid peroxidation and H 2 O 2 overproduction (Fig.…”
Section: Hydrogen Alleviated Boron Toxicity By Modulating Ros Homeostsupporting
confidence: 89%
“…Ample evidence further confirmed that H 2 exhibits potential as a new antioxidant and signalling molecule in preventive and therapeutic applications (e.g. Huang et al, 2010;Kawaguchi et al, 2014;Iuchi et al, 2016). Similar to the approach used in animals, hydrogen-rich water was regarded as a safe and easily available means of investigating the physiological function of endogenous H 2 in plants.…”
Section: Introductionmentioning
confidence: 92%
“…Since the first report in 2007, (5) accumulating evidence has demonstrated its therapeutic potential against IRI and the underlying mechanisms therein. Currently, H 2 i s known to have 3 definitive effects: antioxidant, (5)(6)(7)(8)(9)(10)(11)(12)(13) anti-inflammatory, (10,(14)(15)(16) and antiapoptosis. (8,17) Though some experimental animal studies have shown its therapeutic potential in organ preservation, eg, lung, (11) heart, (18) kidney, (6) intestine, (7) and liver, (19,20) its clinical use is yet to be applied because of its unfavorable features.…”
mentioning
confidence: 99%
“…Recently, Iuchi et al demonstrated that low concentrations (approximately 1%, v/v) of H 2 modulate Ca 2+ signal transduction and regulate gene expression by modifying the production of oxidized phospholipid species [105]. Because H 2 is the smallest as well as a nonpolar molecule, it is unlikely that H 2 could bind to some protein mediators.…”
Section: Molecular Mechanisms Of H2 Efficacymentioning
confidence: 99%